Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Berbantuan Alat Peraga Big Book terhadap Keterampilan Menulis Siswa Kelas III SD - Meyriska, Putri; Wirawan, Gunta; Sumarli, Sumarli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the influence of the CIRC learning model assisted by Big Book teaching aids on the writing skills of class III students at SD Negeri 17 Singkawang. The type of research was quantitative research using the Quasi Experimental method, Posttest Only Nonequivalent Groups Design. The population of this study was all class III students consisting of classes IIIA, IIIB, and IIIC, totaling 86 students. The sample in this study was selected using a purposive sampling technique consisting of class IIIB as the control class and IIIC as the experimental class, each with 28 students. The data collection technique used an essay test technique which contains indicators of writing skills and observation techniques for learning implementation. The data analysis technique used a independent two sample t-test, effect size, and percentage of learning implementation. The results of the research showed that (1) there was differences in the writing skills of third grade elementary school students between classes that use the CIRC model assisted by Big Book teaching aids and classes that use direct learning with the calculation results showing namely 14.068 > 1.674; (2) the CIRC learning model assisted by Big Book teaching aids had a high influence on the writing skills of third grade elementary school students with an effect size calculation result of 2.36; (3) implementation of the CIRC learning model assisted by Big Book teaching aids in learning energy source material with a percentage of 92.71% in very good criteria. Thus, it could be concluded that there was an influence of the CIRC model assisted by Big teaching aids on the writing skills of class III students at SD Negeri 17 Singkawang.